Evaluation of vascular stiffness secondary to vascular calcifications in ambulatory dialysis patients - Mircea Călin Țandrău; Cristina Vîrjan; Oana Știrbu; Daniela-Adriana Oatiș (Romanian Medical Journal, 2021)
Arterial stiffness provides an indirect picture of vascular calcifications in terms of the effect they have on the systemic circulation and consequently on the heart. The present study sought to demonstrate the usefulness of outpatient investigation of vascular calcifications in dialysis patients using pulse wave velocity (PWV) determination. The aim of the study was to determine arterial resistance in patients with chronic dialysis kidney disease. The average study period was 48.5 ± 19.0 (SD) months. The study included 203 patients on dialysis with BCRT. The determination of arterial stiffness was measured at an interval of one hour after the dialysis session. The study highlighted the presence of an increased cardiovascular risk related to the presence of vascular calcifications without being able to establish a direct linear and causal link between their presence, location and the risk of cardiovascular events. The importance of highlighting calcifications and the consequences they generate means the possibility of influencing the main elements that can generate acute cardiovascular events. The results obtained and the correlations performed give an overview of the pathology studied, providing premises for therapeutic influence and risk assessment.